Home-system design & system measurement of gait parameters to prevent fall in elderly people - Teguh Chandra. (2009)
Falls are among the most common and serious problems facing elderly persons. Falling is associated with considerable mortality and reduced functioning. Frequently, older people are not aware of their risks of falling, and neither recognizes the sign of fall. Sign of fall can be found from analyzing of gait pattern. The objective of this research is to study which gait pattern related to the risk of fall and also to create a device which is able to obtain the gait parameter.